The Combined Elevation Test (CET) in Adolescent School Children: A Pilot Study - James Furness; Ben Schram; Darren Corea; Zachary Turner; Hannah Cairns (MDPI AG, 2018)
The Combined Elevation Test (CET) is a musculoskeletal screening technique (MST) that replicates the streamline position in swimming and is commonly used in various sports. Although CET is widely used, no normative data exist within an adolescent population. Therefore, the purpose of this study was to develop a large data set for the CET within an adolescent population and to evaluate the influence of various demographic and anthropometric variables. Data were collected for 416 participants aged between 8 and 18 years old. Age and arm span showed a significant correlation with CET scores (arm span rs (105) = 0.478, p = 0.000; age rs (416) = 0.238, p = 0.000). Regression analysis further quantified the influence of arm span and age on CET scores, accounting for 23.1% and 5.3% of variability respectively. These results can be used as a reference point for clinicians and coaches who are using the CET within their assessments.